Effects of cell morphology, physiology, biochemistry and CHS genes on four flower colors of Impatiens uliginosa - Zhao, Lu-Qiu; Liu, Yang; Huang, Qi; Gao, Shan; Huang, Mei-Juan; Huang, Hai-quan (Frontiers in Plant Science, 2024)
Flower color is one of the important ornamental traits in the plants, which plays an active role in attracting pollinators to pollinate plants and reproduce their offspring. The flower color of Impatiens uliginosa is rich, there are four main flower colors in nature: deep red, red, pink, and white. However, it remains unclear whether on four different flower colors mechanism of I. uliginosa. In this study, we evaluated the effects of different factors on floral coloration during the full-bloom stage of four different flower colors of I. uliginosa. The results of colorimetric measurements showed that the L * and b * values were the highest in white flower, while the a * values were the highest in pink flower. The same shape of epidermal cells was observed in different flower colors, which was all irregular flat polygons, and there were partial lignification. Their cellular pH values were weakly acidic, while the pH values of the deep red flower was the highest and the white flower was the lowest. The highest pigment content of the four flower colors was total anthocyanin content. And it was found that 15 pigment components such as malvidin-3-galactosidechloride (C23H25ClO12), cyanidin-3-O-glucoside (C21H21O11) and delphinidin (C15H11O7) were the main pigment components affecting the color of the petals of four different flower colors. The anthocyanin synthesis gene IuCHS was expressed in four flowers, and all three copies of it had the highest expression level in pink flower and the lowest expression level in white flower. The results of this study revealed the influence of main internal factors on four different flower colors of I. uliginosa, and provided a basis for further understanding of the intracellular and molecular regulatory mechanisms of flower color variation, and laid a foundation for the improvement of flower color breeding of Impatiens.